Petrophysical and Geomechanical characterization of Roseneath and Murteree Formations, Cooper Basin, Australia - IQBAL, OMER (2018)
The Permian and lacustrine Roseneath and Murteree shales are typical potential shale gas reservoirs in Cooper Basin. The multistage hydraulic fracturing and modelling are required to exploit these low permeable rocks. However, currently no universal method exists for selection of suitable layers for fracturing in order to enhance production.